Association between composite dietary antioxidant index and handgrip strength in American adults: Data from National Health and Nutrition Examination Survey (NHANES, 2011-2014) - Dongzhe Wu; Dongzhe Wu; Hao Wang; Wendi Wang; Chang Qing; Weiqiang Zhang; Xiaolin Gao; Yongjin Shi; Yanbin Li; Zicheng Zheng (Frontiers in Nutrition, 2023)
BackgroundThe Composite Dietary Antioxidant Index (CDAI), a composite score of multiple dietary antioxidants (including vitamin A, C, and E, selenium, zinc, and carotenoids), represents an individual’s comprehensive dietary antioxidant intake profile. CDAI was developed based on its combined effect on pro-inflammatory markers Tumor Necrosis Factor-α (TNF-α) and anti-inflammatory effects of Interleukin-1β (IL-1β), which are associated with many health outcomes, including depression, all-cause mortality, colorectal cancer, etc. Handgrip strength is used as a simple measure of muscle strength, not only is it highly correlated with overall muscle strength, but also serves as a diagnostic tool for many adverse health outcomes, including sarcopenia and frailty syndromes.PurposeThe association between CDAI and Handgrip strength (HGS) is currently unclear. This study investigated the association between CDAI (including its components) and HGS in 6,019 American adults.MethodThe research data were selected from the 2011–2014 National Health and Nutrition Survey (NHANES), and a total of 6,019 American adults were screened and included. A weighted generalized linear regression model was used to evaluate CDAI (including its components) and HGS.Results(1) CDAI was significantly positively correlated with HGS (β = 0.009, 0.005∼0.013, P < 0.001), and the trend test showed that compared with the lowest quartile of CDAI, the highest quartile of CDAI was positively correlated with HGS (β = 0.084, 0.042∼0.126, P = 0.002) and significant in trend test (P for trend < 0.0100). Gender subgroup analysis showed that male CDAI was significantly positively correlated with HGS (β = 0.015, 0.007∼0.023, P = 0.002), and the trend test showed that compared with the lowest quartile of CDAI, the highest quartile of CDAI was positively correlated with HGS (β = 0.131, 0.049∼0.213, P = 0.006) and the trend test was significant (P for trend < 0.0100). There was no correlation between female CDAI and HGS, and the trend test was not statistically significant (P > 0.05). (2) The intake of dietary vitamin E, Zinc and Selenium showed a significant positive correlation with HGS (β = 0.004, 0.002∼0.007, P = 0.006; β = 0.007, 0.004∼0.009, P < 0.001; β = 0.001, 0.001∼0.001, P < 0.001), vitamin A, vitamin C and carotenoid were significantly associated with HGS in the Crude Model, but this significant association disappeared in the complete model with the increase of control variables. Gender subgroup analysis showed that in model 3, male dietary intake levels of vitamin E, Zinc, and Selenium were significantly positively correlated with HGS (β = 0.005, 0.002∼0.009, P = 0.011; β = 0.007, 0.004∼0.011, P = 0.001; β = 0.001, 0.001∼0.001, P = 0.004), the rest of the indicators had no significant correlation with HGS. Among the female subjects, dietary zinc intake was significantly positively correlated with HGS (β = 0.005, 0.001∼0.008, P = 0.008), and there was no significant correlation between other indicators and HGS (P > 0.05).ConclusionThere was an association between the CDAI and HGS, but there was a gender difference, and there was an association between the CDAI and HGS in male, but the association was not significant in female. Intake of the dietary antioxidants vitamin E, selenium, and zinc was associated with HGS in male, but only zinc was associated with HGS among dietary antioxidants in female.